PENERAPAN KERJASAMA PEMERINTAH SWASTA DALAM PENYEDIAAN AIR BERSIH DI KOTA DUMAI TAHUN 2019 - Vinsensius, Chairul; Handoko, Tito (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Clean water is an important element in human daily life. The fulfillment of clean water is one of indicator of the level of quality of life humans in an area. The problem of this research is inability PDAM Dumai City in providing clean water services in Dumai City as a service providers that are given the authority of the Dumai City Government to selve the problem of clean water in Dumai City. One of the efforts to overcome the problem of clean water in Dumai City by means public private partnership. This study aims to determine the process of implementing public private partnership to overcome the problem of providing clean water in Dumai City, the impact of public private partnership in improving clean water services and factors what are the obstacles to public private partnership (PPP) in providing clean water in Dumai City in 2019. Approach this research that used is a qualitative approach and this type of research is descriptive. The location of this research was carried out at the Tirta Bersemai Regional Drinking Water Company Dumai City, Dumai City Public Works amd Spatial Planning Service, and PT. Dumai Tirta Persada. Data collection techniques were carried out by interview and documentation. The results of this study in the application of public private partnership in the provision of clean water in Dumai City has been going quite well, it can be seen from service coverage, quality, quantity and continuity of cleawn water enhancement. The construction of clean water supply system in Dumai city has become a consideration for PDAM Dumai City because of ots inability to provide clean water service in Dumai City. And become an inhibiting factor in implementation of public private partnership in the provision of clean water in the City of Dumai is that it takes a long ti,e in terms of abtaining a building permit buildings and from the quality of raw water which is very difficukt to treat. Keywords : Service, Public Private Partnership, PDAM.